USE OF GIS TECHNOLOGIES IN THE STUDY OF THE EFFECT OF POWER LINES ON BIOLOGICAL ORGANISMS AND AGROCHEMICAL CHARACTERISTICS OF SOILS - Marupov Azizkhon Abboskhonovich (Western European Studies, 2024)
This thesis examines the influence of electromagnetic waves emitted by power lines (PTL) on biological organisms and soil resources. Special attention is paid to the integration of geographic information systems (GIS) and soil agrochemistry for the analysis and mapping of impact zones. GIS technologies are used to visualize the results of agrochemical analyses, which makes it possible to identify changes in the chemical composition of soils and assess the impact of EMC on the Ecosystem. An integrated approach that combines well logging and agrochemistry facilitates more accurate and detailed research, as well as the development of measures to minimize negative impacts.
Keywords: electromagnetic waves; power lines; biological organisms